Oral Presentation No. 112 Treatment of pulmonary embolism after paradoxical stroke. (21st October 2022) - Martinho, Mariana; Cotrim, Nuno; Ferreira, Melanie; Calé, Rita; Ferreira, Filipa; Grilo, Vilma; Gisca, Eugeniu; Fonseca, Ana Glória; Gomes, Ana; Judas, Tiago; Pereira, Hélder; Delerue, Francisca
Abstract: Introduction: A patent foramen ovale (PFO) is often diagnosed in cryptogenic strokes and concurrent pulmonary embolism (PE) may be associated. Although often asymptomatic and with low recurrence risk, the best therapy is controversial. Purpose: To study the results of oral anticogulation (OAC) in this population. Methods: Retrospective single-centre study (2015–2020) of pts with asymptomatic PE diagnosed after a paradoxical stroke due to a PFO. Results: Forty pts were included. Mean age was 56 ± 11 years and 55% were female. At diagnosis, 27.5%, 50.0%, 17.5% and 5.9% had none, weak, moderate and strong predisposing factors for PE, respectively. Most pts had peripheral events: 60.0% subsegmental, 37.5% segmental and 2.5% lobar. Regarding treatment, 97.5% initiated OAC (90.0% direct OAC, 7.5% vitamin K antagonist); 1 pt single antiaggregation; 30% had percutaneous PFO closure. Mean clinical follow-up (FUP) was 32 ± 22 months. There was 1 recurrent PE and 1 non-cardiovascular death. Mean time under OAC (TUOAC) was 27 ± 26 months. The only predictor of OAC suspension was PFO closure (17.9% vs. 50.0%, P = 0.037). Of these pts, 50.0% suspended OAC after the procedure (TUOAC 23.2 ± 17.9 months); the remaining had a TUOAC of 28.9 ± 29.9 months. Age or PE predisposing factors were not associated with OAC suspension or TUOAC. There were 3 clinically relevant haemorrhagic events (1 BARC3a, 1 BARC3b, 1 BARC3c). TUOAC was neither associated with bleeding ( P = 0.307) nor with perfusion defects resolution in FUP scintigraphy (55.5 vs. 16.0 months, P = 0.172). Conclusions: TUOAC was not associated with perfusion defects resolution, ischemic or bleeding events. Management of these pts needs more evidence and consensus.